To complete the proof that \( m \) is the midpoint of \( AB \), you would typically follow a logical sequence. Here’s how you might match reasons with statements in the proof:
-
Given: \( AB = 28 \)
Reason: This is a statement of the given information. -
Definition of Midpoint: A point \( m \) is the midpoint of segment \( AB \) if \( AM = MB \) and \( AB = AM + MB \).
Reason: Definition of a midpoint. -
Assume \( AM + MB = AB \): Since \( m \) lies on line \( AB \), we can express \( AM + MB \) where \( AM \) and \( MB \) are the lengths from \( A \) to \( m \) and \( m \) to \( B \).
Reason: Segment addition postulate. -
Set up the equation using the given length: If \( m \) is the midpoint, \( AM = MB \). Hence, \( AM + MB = 2(AM) = 28 \).
Reason: Substitution based on the assumption. -
Solve for \( AM \): \( 2(AM) = 28 \) implies \( AM = 14 \) and \( MB = 14 \).
Reason: Algebraic manipulation. -
Conclude: Since \( AM = MB \) and both are equal to \( 14 \), by definition, \( m \) is the midpoint of \( AB \).
Reason: The conclusion follows from the definition of a midpoint.
By following these steps, you can successfully complete the proof that \( m \) is indeed the midpoint of \( AB \).